2014
DOI: 10.1155/2014/186768
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Indium Recovery and Separation from LCD Waste by Solvent Extraction with Bis(2-ethylhexyl) Phosphate (D2EHPA)

Abstract: Indium tin oxide (ITO) is currently the choice of electrode material in liquid crystal displays (LCDs). D2EHPA is known to be an extractant that can be used to selectively recover indium from 1 M sulfuric acid. In order to optimize the extraction and separation of indium from LCD waste, the effects of pH, temperature, time, and extractant concentration on the distribution ratios of In(III) and the major impurities such as Al(III), Cu(II), Fe(III), and Zn(II) were investigated. Metal concentrations in the aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
1
13
1
2
Order By: Relevance
“…The separation factor represents the selectivity between these two metals in the extraction [26]. Many authors [26,27] have reported that the extraction of the REEs with organophosphorous extractants (here called HR) occurs according to the reaction path described in Eq. 3: ð3Þ where M 3?…”
Section: Theorymentioning
confidence: 99%
“…The separation factor represents the selectivity between these two metals in the extraction [26]. Many authors [26,27] have reported that the extraction of the REEs with organophosphorous extractants (here called HR) occurs according to the reaction path described in Eq. 3: ð3Þ where M 3?…”
Section: Theorymentioning
confidence: 99%
“…Ein Schwerpunkt der gegenwärtigen Untersuchungen liegt auf dem Recycling von LCD-Bildschirmen mithilfe der Flüssig/Flüssig-Extraktion. Das am intensivsten untersuchte Extraktionsmittel ist DEHPA (Bis (2-ethylhexyl)phosphat), das zur Konzentration und Abtrennung von Indium von Begleitmetallen eingesetzt wird [9][10][11][12]. Zwar extrahiert es Indium effektiv bei niedrigem pH-Wert, das extrahierte Metall ist jedoch aus der organischen Phase nur mit konzentrierten Säuren und damit auch nur schwer wiederzugewinnen, was der Grund für die Suche nach alternativen Extraktionsmitteln war.…”
Section: Introductionunclassified
“…Solvent extraction (SX) is a well-established technique, which is widely used in industry to remove and recover metal ions from aqueous phases. Various organic solvents such as LIX 973N [2], a mixture of different phosphine oxides (Cyanex 923) [3], bis-(2,4,4-trimethylpentyl) phosphinic acid (Cyanex 272) [4][5], di(2-ethylhexyl)phosphoric acid (D 2 HPA) [6][7][8][9], tributyl phosphate (TBP), a mixture of D 2 EHPA and TBP [10] and PC88A [11][12] have been studied for indium extraction. Among them, organophosphorus extractants in kerosene are the most practical for the extraction of trivalent ions due to their stability, high distribution ratio for metal extraction, low water solubility and high selectivity for metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, n-octanol was found to be the worse diluent for this system. Later in 2014, Yang and his research team [8] have studied the effects of pH, concentration of extractant, temperature and stripping agents for indium extraction. They found that more indium was extracted when the operating temperature was lower than 293 K and 1 M H 2 SO 4 was the best stripping agent to recover indium from the loaded organic phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation